2019
DOI: 10.3390/en12234574
|View full text |Cite
|
Sign up to set email alerts
|

Large-Eddy Simulation of Yawed Wind-Turbine Wakes: Comparisons with Wind Tunnel Measurements and Analytical Wake Models

Abstract: In this study, we validated a wind-turbine parameterisation for large-eddy simulation (LES) of yawed wind-turbine wakes. The presented parameterisation is modified from the rotational actuator disk model (ADMR), which takes account of both thrust and tangential forces induced by a wind turbine based on the blade-element theory. LES results using the yawed ADMR were validated with wind-tunnel measurements of the wakes behind a stand-alone miniature wind turbine model with different yaw angles. Comparisons were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 40 publications
6
34
0
Order By: Relevance
“…The analytical model of Jiménez et al (2009) overestimates the wake deflection, and the models by Bastankhah and Porté-Agel (2016) and Qian and Ishihara (2018) better match the wake deflection from the field measurements. The overestimation of the Jiménez et al (2009) model was also observed by Bastankhah and Porté-Agel (2016) with wind tunnel experiments and by Lin and Porté-Agel (2019) with numerical simulations. The measurement data show considerably larger scattering than the model predictions, which is likely a consequence of the remaining non-stationarity of the atmospheric boundary layer in the data set and the measurement errors of the yaw angle.…”
Section: Wake Deflectionsupporting
confidence: 65%
See 2 more Smart Citations
“…The analytical model of Jiménez et al (2009) overestimates the wake deflection, and the models by Bastankhah and Porté-Agel (2016) and Qian and Ishihara (2018) better match the wake deflection from the field measurements. The overestimation of the Jiménez et al (2009) model was also observed by Bastankhah and Porté-Agel (2016) with wind tunnel experiments and by Lin and Porté-Agel (2019) with numerical simulations. The measurement data show considerably larger scattering than the model predictions, which is likely a consequence of the remaining non-stationarity of the atmospheric boundary layer in the data set and the measurement errors of the yaw angle.…”
Section: Wake Deflectionsupporting
confidence: 65%
“…Both 2D and 3D scans of wake-scanning lidar for control cases with a successfully detected wake centre are used. merical simulations (Lin and Porté-Agel, 2019). The analytical model of Jiménez et al (2009) overestimates the wake deflection, and the models by Bastankhah and Porté-Agel (2016) and Qian and Ishihara (2018) better match the wake deflection from the field measurements.…”
Section: Wake Deflectionmentioning
confidence: 75%
See 1 more Smart Citation
“…The wind turbine forcing is represented by f i and an actuator disk model is used (Calaf et al, 2010). While the actuator disk model is lower fidelity than the actuator line methods, it captures the far wake accurately for both aligned (Martínez-Tossas et al, 2015) and yaw misalignment wind turbines (Lin and Porté-Agel, 2019). Since the goal of the present study is controller synthesis and sensitivity experiments, more computationally expensive actuator line simulations are left for future work given the large volume of simulations that are run.…”
Section: Large Eddy Simulation Setupmentioning
confidence: 99%
“…Linear superposition of the individual wakes is assumed in Eq. (1) (Lissaman, 1979). The wake centerline y c, i is given by…”
Section: Lifting Line Wake Modelmentioning
confidence: 99%